Psychological factors of economic decision-making process - E. S. Mishenin (Вестник университета)
Personality-psychological aspects inﬂuencing an individual’s economic behavior have been studied. It has been analyzed how cognitive abilities and personality characteristics inﬂuence the decision-making process under uncertainty. Theoretical concepts and empirical studies proving the signiﬁcance of subjective and unconscious factors, such as emotions, biases, and risk perception, when forming complex patterns of economic behavior have been considered. The information processing mechanisms and decision-making stages in the context of economic activity have been considered. It has been demonstrated that psychological factors play a key role in investment and consumer decisions. It has been emphasized that the process of making economic decisions, such as choosing a production object, pricing policy, use of technology, taxation system, consumer choice, and investment, has its own speciﬁcs. The importance of considering general psychological regularities, a manager’s personal characteristics, risk management, and a systematic approach application has been studied. Special attention has been paid to the importance of subjective and unconscious phenomena, such as prejudices and stereotypes, which predetermine complex behavioral patterns of the economic sphere subjects. The study of these factors presents a prospect for further research in the ﬁeld of psychology and economics, contributing to a deeper understanding of decision-making mechanisms and effective strategies development in economic activity management.